Municipal Solid Waste to Energy: Palletization of Paper and Garden Waste into Refuse Derived Fuel - Suryawan, I.W.K. (Polskie Towarzystwo Inzynierii Ekologicznej (PTIE), 2022)
The purpose of this research was to process a mixture of paper waste and garden waste based on material flow analysis and to analyze its parameters based on water content, ash content, heating value, along with Thermogravimetry Analysis (TGA)/Derivative Thermogravimetry (DTG). The garden waste treatment process consists of shredding, drying with a rotary dryer, separator, and then shaving with a hammer mill. Paper waste only needs a shredder process. Then, the mixing process and pelletizing of paper waste as well as garden waste are carried out according to the variation (w/w) 100 paper (K100), 75 paper (K75), 50 paper (K50), 25 paper (K25), and 100 garden waste (K0). The water content ranged from 5.8 to 15.25. From K0 to K100 samples, the ash content increased from 4.54 to 9.85. A correlation of 0.9047 was found from samples K0 to K100. There was a correlation between increasing calorific value along with the mixture with paper waste. The caloric value in K0 to K100 increased from 13.11 to 19.03 MJ/kg. The TGA/DTG analysis reduced mass due to water evaporation, devolatilization, and carbonization processes. Â© 2022, Journal of Ecological Engineering. All rights reserved.